Respostas

2013-04-07T21:10:13-03:00

f(x) = x²-5x 

f(2) = 2² - 5 · 2 

          4 - 10

            -6

 

f(-2) = -2² - 5 · (-2) 

            4 + 10 

               14

 

f(2+x) = (2+x)² - 5 · (2+x)

             4 + x² - 10 -5x

             x² - 5x - 6

         Δ = b² - 4ac                x = (-b ± √Δ)/2a

         Δ = (-5)² - 4·1·(-6)      x = (-(-5) ± √49)/2·1

         Δ = 25 + 24                x = (5 ± 7)/2

         Δ = 49                        x₁= 12/2 = 6

                                            x₂= -2/2 = -1

      

1 5 1